Functional performance tests in interstitial lung disease: Impairment and measurement properties. (August 2021) - Zamboti, Camile Ludovico; Gonçalves, Aline Ferreira Lima; Garcia, Thatielle; Krinski, Gabriela Garcia; Bertin, Larissa Dragonetti; Almeida, Heloiza dos Santos; Pimpão, Heloise Angélico; Fujisawa, Dirce Shizuko; Ribeiro, Marcos; Pitta, Fabio; Camillo, Carlos Augusto
Abstract: Background: There is limited information regarding impairment in functional performance tests and their measurement properties in ILD. The present study aimed to verify the impairment and measurement properties of functional performance tests in ILD. Methods: ILD and healthy individuals underwent assessments of pulmonary function, peripheral muscle strength (handgrip force and maximum isometric contraction of quadriceps femoris – MIVCq) and exercise capacity (6-min walk test – 6MWT). Functional performance was assessed by timed-up-and-go with usual (TUGu) and fast (TUGf) gait speeds, 4-m gait speed (4MGS), sit-to-stand in 30 s (30sec-STS), 1 min (1min-STS) and with 5 repetition (5rep-STS) and Short Physical Performance Battery (SPPB). Functional performance was compared between groups, validity (correlation with 6MWT and MIVCq) and reliability of tests were checked in subjects with ILD (intra- and inter-rater agreement analysis). Results: Seventy-six participants (40 ILD [25 women, 61 ± 11 years, FVC 75 ± 17 %pred] and 36 healthy [22 women, 61 ± 9 years, FVC 97 ± 11 %pred]) were included. Functional performance in ILD was worse than in healthy individuals in all tests, except for the 30sec-STS (p = 0.13). Pre-specified validity criteria were reached for TUGu, TUGf, 4MGS and 5rep-STS (−0.69 < r < 0.55; p < 0.05 for all). Except for 4MGS and SPPB, all tests showed good to excellent inter-rater (0.85 < ICC<0.93; p < 0.05 for all) and all tests showed good to excellent intra-rater (0.83 < ICC< 0.94; p < 0.05 for all) reliability. Conclusions: Subjects with ILD present worse functional performance than healthy individuals. According to reliability and validity results, TUGu, TUGf and 5rep-STS seem to be the most appropriate tests to evaluate functional performance in ILD. Highlights: ILD patients present worse functional performance compared to healthy individuals. TUG, 4MGS and 5rep-STS are valid functional tests in ILD. Except for 4MGS and SPPB in inter-rater analysis, all tests are reliable. TUG and 5rep-STS seem to be the most appropriate tests to assess functionality in ILD.